Characterization of Intramolecular Disulfide Bonds and Secondary Modifications of the Glycoprotein from Viral Hemorrhagic Septicemia Virus, a Fish Rhabdovirus - Einer-Jensen, Katja (American Society for Microbiology, 1998)
Viral hemorrhagic septicemia virus (VHSV) infections cause high losses in cultured rainbow trout in Europe. Attempts to produce a recombinant vaccine based on the transmembrane glycoprotein (G protein) have indicated that proper folding is important for the antigenicity and immunogenicity of the protein. The present study was initiated to identify the disulfide bonds and other structural aspects relevant to vaccine design. The N-terminal amino acid residue was identified as being a pyroglutamic acid, corresponding to Gln21 of the primary transcript. Peptides from endoproteinase-degraded G protein were analyzed by mass spectrometry before and after chemical reduction, and six disulfide bonds were identified: Cys29-Cys339, Cys44-Cys295, Cys90-Cys132, Cys172-Cys177, Cys195-Cys265, and Cys231-Cys236. Mass spectrometric analysis in combination with glycosidases allowed characterization of the glycan structure of the G protein. Three of four predicted N-linked oligosaccharides were found to be predominantly biantennary complex-type structures. Furthermore, an O-linked glycan near the N terminus was identified. Alignment of the VHSV G protein with five other rhabdovirus G proteins indicates that eight cysteine residues are situated at conserved positions. This finding suggests that there might be some common disulfide bonding pattern among the six rhabdoviruses.